MODELING OF GEOCHEMICAL PROCESSES OCCURRED DURING THE FORMATION OF THE SCHLEMA DEPOSIT, ERZGEBIRGE. II. FORMATION OF PRE-URANIUM VEINS - Barsukov V.L. (My University, 2006)
By means of computer modeling, it was shown that the pre-uranium quartz and quartz-sulfide veins of the Schlema deposit with their typomorphic assemblages could be formed at the expense of cooling of hot pore solutions from the Aue granite cupola underlying the mineralized zones. As was shown previously [1], the ore metal content of these pore solutions changes with decreasing temperature and pressure in the granite-water system and an increase in the intensity of granite "flushing" with a water phase. The dependence of the composition of precipitated material on the proportions of chlorides and carbon dioxide in the pore solutions was evaluated in the models. It was shown that silica mobilization from the granite and redeposition were accompanied by the oxidation of ferrous iron in the granite and extraction of sulfide sulfur in molal amounts similar to or even higher than those of silica. This provided conditions for uranium migration after these stages and formation of hydrothermal uranium ores. © Pleiades Publishing, Inc. 2006.
Keywords: Schlema deposit